A Clustering Framework for Monitoring Circadian Rhythm in Structural Dynamics in Plants From Terrestrial Laser Scanning Time Series - Puttonen, Eetu; Lehtomäki, Matti; Litkey, Paula; Näsi, Roope; Feng, Ziyi; Liang, Xinlian; Wittke, Samantha; Pandžić, Miloš; Hakala, Teemu; Karjalainen, Mika; Pfeifer, Norbert (Frontiers in Plant Science, 2019)
Terrestrial Laser Scanning (TLS) can be used to monitor plant dynamics with a frequency of several times per hour and with sub-centimetre accuracy, regardless of the external lighting conditions. TLS point cloud time series measured with short intervals produce large quantities of data that require fast processing techniques that have to be robust to noise inherent in the point clouds. This study presents a general framework to monitor diurnal plant movements from TLS time series. The framework performance was evaluated using TLS time series collected from two Norway maples (Acer platanoides) and a control target, lamp post. The results showed that the presented processing framework can capture diurnal movements of a plant with down to one centimetre spatial resolution. The largest movements in both Norway maples were observed before sunrise and at the outer edges of its crown. The individual cluster movements were up to 0.17 m (99th percentile) for the taller Norway maple and up to 0.11 m (99th percentile) for the smaller Norway maple from their initial positions before sunset.